2019
DOI: 10.3390/nu11081913
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Dietary Acid Load and Biomarkers of Inflammation and Hyperglycemia in Breast Cancer Survivors

Abstract: Metabolic acidosis can lead to inflammation, tissue damage, and cancer metastasis. Dietary acid load contributes to metabolic acidosis if endogenous acid–base balance is not properly regulated. Breast cancer survivors have reduced capacities to adjust their acid–base balance; yet, the associations between dietary acid load and inflammation and hyperglycemia have not been examined among them. We analyzed data collected from 3042 breast cancer survivors enrolled in the Women’s Healthy Eating and Living (WHEL) St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 45 publications
3
73
0
Order By: Relevance
“…Chronic consumption of a diet with a high acid load could shift the acid-base balance toward acidosis (21). Besides, with the presence of abnormalities in acid-base balance, the dietary acid load is more likely to induce acidosis in the human body (18). It has been found that people with migraine could have abnormalities in the acid-base balance due to mitochondrial dysfunction (38,39).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Chronic consumption of a diet with a high acid load could shift the acid-base balance toward acidosis (21). Besides, with the presence of abnormalities in acid-base balance, the dietary acid load is more likely to induce acidosis in the human body (18). It has been found that people with migraine could have abnormalities in the acid-base balance due to mitochondrial dysfunction (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that people with migraine could have abnormalities in the acid-base balance due to mitochondrial dysfunction (38,39). Several possible mechanisms have been suggested that a high acidic load may play a role in the onset of migraine attacks or increasing headache attack frequency in migraineurs (16)(17)(18)(19)(20); these are explicated as follows. First, animal and human studies have reported that acidosis can cause high in ammation and NO due to its damaging effect on tissues or blood vessels (16)(17)(18)40).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations